Asia e University Marks Milestone With New Campus - Borneo, Post (Borneo Post, 2018)
Asia e University (AeU) new campus which opened in 2018 marked a milestone in the university's goal of improving its position among Open and Distance Learning (ODL) institutions in Asia.